The Quest for Equitable Growth in the Slovak Republic : A World Bank Living Standards Assessment - World Bank (Washington, DC, 2012)
There is wide agreement that the radical and comprehensive package of reforms implemented by the 2002 government has positioned the Slovak Republic well-not only in relation to other EU8 countries but also in relation to the EU15-in terms of increased competitiveness and employment opportunities, two of the main aims of the EU Lisbon Strategy for Employment and Social Inclusion. However, concerns have also been voiced about the potential negative effect of the reforms on the other dimension of the Lisbon strategy: the drive for social inclusion. The argument is that in view of the pre-existing inequalities in access to employment across regions and individuals, the increased emphasis on work as an individual's right and duty, and as the main route out of poverty, may amplify the economic disadvantages and increase the social exclusion of those who face strong and complex barriers to employment. Little systematic effort has been made to monitor the impact of the reform process begun in 1998 because of data limitations. Within this context, this report provides the following: 1) A baseline analysis of the current performance of the Slovak economy in the areas of employment, labor market segmentation and social exclusion, against which future development can be assessed and evaluated. 2) An assessment (to the extent possible, given the data constraints) of the impact of the far-reaching structural reforms implemented after the 2002 elections on (a) the living standards of the most vulnerable; (b) the distribution of income and welfare; c) job creation and employment opportunities; and (d) the levels of and inequalities in work income. 3) An effort to advise on any actions/policies that may further increase the effectiveness of the recent reforms as a strategy for promoting social inclusion.